Algorithms as work designers: How algorithmic management influences the design of jobs - Parent-Rocheleau, Xavier; Parker, Sharon K. (Human resource management review, 2022)
We review the literature on algorithmic management (AM) to bridge the gap between this emerging research area and the well-established theory and research on work design. First, we identify six management functions that algorithms are currently able to perform: monitoring, goal setting, performance management, scheduling, compensation, and job termination. Second, we show how each AM function affects key job resources (e.g., job autonomy, job complexity) and key job demands (e.g., workload, physical demands); with each of these resources and demands being important drivers of worker motivation and their well-being. Third, rejecting a deterministic perspective and drawing on sociotechnical systems theory, we outline key categories of variables that moderate the link between AM on work design, namely transparency, fairness and human influence (e.g., whether workers can control the system). We summarize our review in the form of a model to help guide research on AM, and to support practitioners and designers in the creation and maintenance of meaningful jobs in the era of algorithms. •The article describes six management functions that AI-enabled algorithms are able to perform.•The influence of each AM function on work design characteristics is reviewed.•We review and discuss parameters likely to mitigate the effects of AM.